Writing South African History: Trends and Retrospect - Elize S van Eeden; Jeff Peires; Jared McDonald; Nigel Worden; Gerald Groenewald; Carolyn Hamilton; John Wright; Goolam Vahed; Mohamed Adhikari; Christopher Saunders; Hans Erik Stolten; Thula Simpson; et al. (AOSIS, 2025)
Writing South African history: Trends and retrospect presents the first comprehensive reassessment of South African historiography in nearly four decades. Across 18 original chapters by leading scholars, it examines how South Africa's past has been written, debated and reimagined amid major political, intellectual and methodological shifts since the late 20th century. The book revisits established liberal, radical, revisionist and nationalist traditions, as well as frontier historiography, while engaging critically with debates on colonialism, settler colonialism, apartheid and decolonisation. The volume broadens the scope of historical inquiry by addressing key thematic and methodological developments, including labour, economic and environmental history, the history of medicine and health, gender and masculinity studies, public and oral history, youth culture and multilingual archival practice. It revisits foundational debates on slavery, the Mineral Revolution, the Mfecane, the Great Trek and the 1976 Soweto Uprising, and analyses historiographical responses to apartheid, anti-apartheid scholarship, African nationalism, the African National Congress, the Black Consciousness Movement and recent student-led protest movements. Moving beyond static historiographical ‘schools', the collection interrogates the evolving craft of the historian through critical reflection on sources, method and interpretation. Particular attention is given to neglected and marginalised traditions, including indigenous, Indian and Coloured historiographies, as well as the histories of San and Khoekhoe communities and enslaved and indigenous Cape inhabitants. Situating South African historiography within global and transnational contexts, the book demonstrates how political change and contemporary movements have reshaped the production of historical knowledge. Written in an accessible style, it offers scholars a rigorous and forward-looking contribution to South African history, African studies and global historiography.